Banking model of corporate waqf: an analysis of Wakaf Selangor Muamalat / Asharaf Mohd Ramli and Abdullaah Jalil - Ramli, Asharaf Mohd; Jalil, Abdullaah (2013)
Purpose - This study aims to analyse the structure of the corporate waqf model applied in "Wakaf Selangor Muamalat" which has been jointly established by Perbadanan Wakaf Selangor (PWS) and Bank Muamalat Malaysia Berhad (BMMB). Design/Methodology/Approach - This is an exploratory study primarily focused on the library research and secondary information. Since "Waqf Selangor Muamalat" was only launched on September 27, 2012, the empirical data of this instrument is not yet available for analysis. Findings - BMMB is the first Malaysian Islamic banking institution which partakes in the accumulating and managing the waqf fund for investment with the State Religious Council. This latest collaboration offers a new dimension of waqf corporate models in Malaysia, specifically as a banking model of corporate waqf. Originality/value - This is the first study on "Waqf Selangor Muamalat" structure since it was launched. The outcome of this study is expected to provide some insight on the potential waqf models that are applicable within the institutional framework of banking sector.